Mysteries of Sex : Tracing Women and Men through American History - Ryan, Mary P. (Book collections on Project MUSE., 2006)
In a sweeping synthesis of American history, Mary Ryan demonstrates how the meaning of male and female has evolved, changed, and varied over a span of 500 years and across major social and ethnic boundaries. She traces how, at select moments in history, perceptions of sex difference were translated into complex and mutable patterns for differentiating women and men. How those distinctions were drawn and redrawn affected the course of American history more generally. Ryan recounts the construction of a modern gender regime that sharply separated male from female and created modes of exclusion and inequity.